Genotoxicity assessment of impacted urban coast using chelon auratus (risso, 1810) - Turan, Funda; Yilmaz, M. Bertan; Yola, M. Lutfi; Ergenler, Aysegul; Ilgaz, N. Seda; Oksuz, Hale (Cahıers De Bıologıe Marıne, 2023)
This study aimed at investigating the genetic damage and the accumulations of trace metals in Chelon auratus (Risso, 1810) by COMET Assay to test whether this species should represent a bioindicator species of the Arsuz coast of Iskenderun Bay, North-Eastern Mediterranean. Fish were seasonally collected at a contaminated sampling site and as a reference material in an aquacultural farm over one year. Physicochemical parameters in water and trace metals in the tissues of fish collected from these sites were obtained by electrochemical techniques. A one-way analysis of variance (ANOVA) was applied for significance assessments. Principal component analysis (PCA) was applied to define the most important parameters involved in DNA damage, and Pearson correlation test was also used to determine the relationship between trace metals and DNA damage. In the present study, Fe, Zn, Cr and Cu concentrations in the water column of sampling site were exceeded the values allowed by the TEG (2015) and EPA (1989) for all seasons. Trace metal concentrations in the liver tissues of C. auratus can be ranged as follows: Fe > Zn > Cu > Mn > Ni > Cr > Co > Pb > Cd > Hg for the sampling site. Fe and Pb accumulations in liver tissues of golden grey mullet exceeded the maximum limits allowed by the TFC (2011) and EU (2005) in Summer and Autumn. The highest levels of DNA damage were detected at the sampling site with 77.67 +/- 1.52% DF, 181.67 +/- 9.71 AU, and 1.81 +/- 0.09% GDI in the gill tissue in the Summer. A significant positive correlation between Fe, Zn, Cu, Hg, Cr and Co accumulations and DNA damage parameters were reported in the present study. Besides, we reported firstly, that the electrochemical technique can be used successfully in the determination of trace metal concentrations in C. auratus. Consequently, obtained ecotoxicological data indicate that C. auratus constitutes a useful tool as a sentinel organism for biomonitoring the coastal ecosystem.
Keywords: DNA damage; Metal; Comet assay; Chelon auratus